2016
DOI: 10.18632/oncotarget.9844
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of Chk1 by p53 plays a role in synergistic induction of apoptosis by chemotherapeutics and inhibitors for Jak2 or BCR/ABL in hematopoietic cells

Abstract: DNA-damaging chemotherapeutic agents activate apoptotic pathways in cancer cells. However, they also activate checkpoint mechanisms mainly involving Chk1 and p53 to arrest cell cycle progression, thus abbreviating their cytotoxic effects. We previously found that aberrant tyrosine kinases involved in leukemogenesis, such as BCR/ABL and Jak2-V617F, as well as Jak2 activated by hematopoietic cytokines enhance Chk1-mediated G2/M arrest through the PI3K/Akt/GSK3 pathway to confer resistance to chemotherapeutic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Since JAK2, STAT3 and PI3K pathways are also involved in several other activities such as apoptosis and senescence, that are two phenomena that could be induced by anticancer drugs, future investigations will be performed in order to evaluate if treatment with reparixin may have any effect on these phenomena as already described by other Authors in different cancer cells [6870]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since JAK2, STAT3 and PI3K pathways are also involved in several other activities such as apoptosis and senescence, that are two phenomena that could be induced by anticancer drugs, future investigations will be performed in order to evaluate if treatment with reparixin may have any effect on these phenomena as already described by other Authors in different cancer cells [6870]. …”
Section: Discussionmentioning
confidence: 99%
“…Overall the results described in this paper for the first time provide evidences that IL-8 and its receptors CXCR1/2 play a key role in the induction and progression of peripheral neuropathy and reinforce the hypothesis that CXCR1/2 inhibitors combined with standard taxane therapy might potentiate the taxane anti-tumor activity and reduce the chemotherapy-induced neurotoxicity. Since JAK2, STAT3 and PI3K pathways are also involved in several other activities such as apoptosis and senescence, that are two phenomena that could be induced by anticancer drugs, future investigations will be performed in order to evaluate if treatment with reparixin may have any effect on these phenomena as already described by other Authors in different cancer cells [ 68 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akt can be activated by the lipid kinase PI3K through generating the second messenger PIP3 (phosphatidylinositol-3,4,5- triphosphate). GSK-3β is an important downstream molecule of Akt, which has close relationship with cellular proliferation, migration, apoptosis, cell cycle and glucose regulation ( Ali et al, 2001 ; Umezawa et al, 2016 ). Activation of the PI3K-Akt-GSK-3β signaling pathway makes the downstream transcription factor Snail more stable to repress the expression of gene CDH 1 encoding E-cadherin, promoting EMT process ( Lamouille et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of quantitative RT-PCR showed that the expressions of P53 mRNA, Fas/FasL mRNA, and MMP-2 mRNA in uterus were significantly elevated after treatment with MPF and the expression of TGF-β1 mRNA was reduced. The expression of P53 mRNA, Fas/FasL mRNA, and MMP-2 mRNA all have an effect to promote the apoptosis (Kitamura et al, 2001;Dmitrieva et al, 2003;Smane et al, 2013;Zhang et al, 2015;Umezawa et al, 2016). High expression of TGF-β1 mRNA can induce the activation of anti-apoptotic cytokine NF-κb, resulting in blocking of inflammatory cells'…”
Section: Discussionmentioning
confidence: 99%